Universal test and treat in relation to HIV disease progression: results from a stepped-wedge trial in Eswatini - Boeke, Caroline E.; Khan, Shaukat; Walsh, Fiona J.; Hettema, A.; Lejeune, C.; Spiegelman, Donna; Okello, V.; Harwell, Joseph; Mazibuko, S.; Bärnighausen, Till (HIV medicine, 2021)
Objectives Universal test and treat (UTT) is recommended for people living with HIV (PLHIV) to reduce morbidity/mortality and minimize transmission. However, concerns exist that this strategy may lead to more crowded hospitals, longer wait times and poorer service, adversely impacting health outcomes for clients with severe disease. We assessed how UTT was related to markers of disease progression in PLHIV overall and specifically among clients with low CD4 count/high World Health Organization (WHO) stage. Methods The analysis was conducted using data from a stepped-wedge trial of UTT in 14 government-managed health facilities in Eswatini from 2014 to 2017. Disease progression was defined as CD4 count falling below 200 cells/µL or baseline value, > 10% weight loss, body mass index (BMI) dropping below 18.5, incident tuberculosis (TB) or HIV-related death; these outcomes also were assessed individually. We assessed multivariate Cox proportional hazard models overall and specifically among clients with CD4 count < 350 cells/μL or WHO stage 3-4 at enrolment. Results Eight hundred and seven of 3176 clients demonstrated at least one marker of disease progression over 2339 person-years of follow-up. Overall, 62.4% of clients were female; 57.2% were < 35 years old. Compared to clients not exposed to UTT, those exposed to UTT had a lower rate of disease progression overall [adjusted hazard ratio (aHR) 0.60; 95% confidence interval (CI) 0.46-0.78] and a lower rate of CD4 decline (aHR 0.40; 95% CI 0.27-0.58). When the analysis was limited to clients with CD4 count < 350 cells/μL or WHO stage 3-4, UTT was not associated with disease progression (aHR 0.92; 95% CI 0.66-1.29). Conclusions UTT reduced HIV disease progression overall and was not detrimental for clients with more severe disease.